Melampaui Politisi, Menuju Negarawan: Refleksi Etis Kristiani - Togardo Siburian (Societas Dei: Jurnal Agama dan Masyarakat, 2017)
ABSTRACT: This article wants to study the possibility of principles of statemen for politician in these days. As we know, most politicians behave an conduct more as a handiman of politics, instead of a statemen (used to be called: politicos). Therefore Christian reflection on ethics became essential to comprehend the imbalance practice and concept that emerged. This studies is done from ethical perspective through library research. Out of the three things mentioned that make political issues today chaotic particularly is: 1) A detached politics from ethics, 2) political study today only focused on law and social studies, 3) and forget philosophical and historical perspective to the study. Based on the way of ethical politics today, we found a principles that enrich ecclesiastical mandate and transformation in society. KEYWORDS: political matters, ethics, politician, statemen, Christian, transformation, mandate, church.